A neglected determinant of eating behaviors: Relative age - Luca Fumarco; Sven Alfred Hartmann; Francesco Principe (University of Trier, Institute for Labour Law and Industrial Relations in the European Union (IAAEU), 2024)
This study investigates a neglected determinant of adolescents' dietary behaviors: the within-class age difference, in isolation from confounding factors (e.g., absolute age, season-of-birth, and countries' specific characteristics, such as expected age at school start). We study a multi-country dataset, with more than 500k students, from dozens of very diverse countries. We find that the youngest students in a class have worse dietary behaviors; they are more likely overweight, they eat fewer vegetables and fruits, they eat more sweets and drink more soft drinks, they tend to skip breakfast, go to bed hungry, and be on a diet. These findings are likely to reflect peer effects: two students with the same absolute age, who were born in the same season, and started school at the same time, have different dietary behaviors because of how their age compares to that of their classmates. Finally, we show that this result holds across countries, which demonstrate the ubiquity of relative age effects on eating behaviors.
Keywords: I12; I18; I24; 330; Diet; Adolescence; Causal; External validity; Relative age